Perfluoroalkyl substituted allyl quaternary ammonium salt and preparation method thereof, copolymer and preparation method and application thereof, and wastewater treatment method

By introducing a copolymer of perfluoroalkyl-substituted allyl quaternary ammonium salt and acrylamide into the flocculant, the problem of poor salt resistance of conventional flocculants in high-salt environments is solved, and efficient natural gas purification industrial wastewater treatment is achieved.

CN119707709AActive Publication Date: 2025-03-28PETROCHINA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311252219.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

In the prior art, conventional cationic polyacrylamide flocculants have poor salt resistance in high-salt environments, their molecular chains are prone to curl, and their bridge capacity is lost, and they cannot effectively treat natural gas purification industrial wastewater with high sulfate and high organic amines.

Method used

Perfluoroalkyl-substituted allyl quaternary ammonium salt is used as fluoro-containing cationic hydrophobic monomer and polymerized with acrylamide to form a copolymer flocculant. This flocculant still maintains a three-dimensional network structure in a high-salt environment, has a strong hydrophobic association effect and good bridge building ability.

Benefits of technology

This copolymer flocculant can effectively shorten the flocculation time under high salt conditions, improve the flocculation effect, significantly improve the treatment effect of natural gas purification industrial wastewater, and avoid the problem of flocculant molecular chain curling under high salt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707709A_ABST
    Figure CN119707709A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of natural gas purification industrial wastewater treatment, and discloses perfluoroalkyl substituted allyl quaternary ammonium salt and a preparation method thereof, a copolymer and a preparation method and application thereof, and a wastewater treatment method. The quaternary ammonium salt has a structure as shown in a formula (1), # imgabs0 # formula (1), and R1 and R2 are respectively and independently selected from methyl or ethyl; and n is an integer from 4 to 11. The quaternary ammonium salt is obtained through a nucleophilic substitution reaction between allylamine or a derivative thereof and perfluoroalkyl haloalkane. The copolymer contains a structural unit A derived from acrylamide and a structural unit B derived from the quaternary ammonium salt, and is obtained by polymerization reaction between acrylamide and the quaternary ammonium salt monomer. The copolymer disclosed by the invention has better salt tolerance and stronger hydrophobic association effect, and can be well adapted to high-salt industrial wastewater treatment or impurity removal in the field of natural gas purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment in the natural gas purification industry, and in particular to a perfluoroalkyl-substituted allyl quaternary ammonium salt and a preparation method thereof, a copolymer and a preparation method and application thereof, and a method for treating wastewater. Background Art

[0002] As my country actively promotes the green transformation of its energy structure, natural gas plays a vital role as a green, efficient and low-carbon fossil energy. It is well known that high-salt organic industrial wastewater will be generated in the exploration, development, production, gathering, transportation and purification and processing of sour natural gas, shale gas and tight gas. In particular, with the vigorous development of deep and ultra-deep sour natural gas in recent years, the total production and discharge of high-salt organic wastewater in the natural gas industry has continued to increase. For example, the oxidation absorption process of tail gas in natural gas purification plants has been gradually applied to natural gas purification. The process is to directly incinerate various sulfides in the tail gas of the sulfur recovery unit of the natural gas purification plant, convert them into SO2, and absorb SO2 with highly selective organic amines after cooling, in which the organic amine absorption solution can be regenerated and recycled at high temperature, and the regenerated high-concentration SO2 gas is returned to the sulfur recovery unit. However, the amine liquid purification link of this process will produce a large amount of high-sulfate organic amine industrial wastewater, which needs to be treated urgently.

[0003] The coagulation-flocculation method is widely used in the treatment of industrial wastewater from natural gas purification. The key to this method is to use a suitable flocculant. Organic polymer, inorganic, microbial and composite flocculants are the more commonly used flocculants, among which polyacrylamide polymer flocculants are the most widely studied and applied. However, for industrial wastewater from natural gas purification with high sulfate and high organic amine content, conventional cationic polyacrylamide flocculants often have poor salt tolerance, are prone to molecular chain curling under high salt conditions, lose bridging ability, and cannot achieve a good flocculation treatment effect. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of poor salt resistance of conventional cationic polyacrylamide flocculants in the prior art, easy molecular chain curling and loss of bridging ability under high salt conditions, and inability to achieve a good flocculation treatment effect, and to provide a perfluoroalkyl-substituted allyl quaternary ammonium salt and a preparation method, a copolymer and a preparation method and application, and a method for treating wastewater.

[0005] In order to achieve the above object, the present invention provides a perfluoroalkyl-substituted allyl quaternary ammonium salt in a first aspect, wherein the quaternary ammonium salt has a structure shown in formula (1): Formula (1), wherein R1 and R2 are independently selected from methyl or ethyl; and n is an integer of 4-11.

[0006] The second aspect of the present invention provides a method for preparing a perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the method comprises: subjecting N,N-dimethylallylamine or N,N-diethylallylamine to a nucleophilic substitution reaction with a perfluoroalkyl halide to obtain the perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the molar ratio of N,N-dimethylallylamine or N,N-diethylallylamine to the perfluoroalkyl halide is 1:1.2-1.5.

[0007] The third aspect of the present invention provides a perfluoroalkyl-substituted allyl quaternary ammonium salt prepared by the preparation method provided by the second aspect of the present invention.

[0008] The fourth aspect of the present invention provides a copolymer, wherein the copolymer comprises: a structural unit A derived from acrylamide and a structural unit B derived from a perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the perfluoroalkyl-substituted allyl quaternary ammonium salt is the perfluoroalkyl-substituted allyl quaternary ammonium salt described in the present invention, and the molar ratio of the structural unit A:structural unit B is 196-199:1-4.

[0009] A fifth aspect of the present invention provides a method for preparing a copolymer, wherein the method comprises: polymerizing acrylamide and a fluorine-containing cationic hydrophobic monomer in the presence of an initiator and a protective gas to obtain the copolymer.

[0010] The sixth aspect of the present invention provides a copolymer prepared by the preparation method provided by the fifth aspect of the present invention.

[0011] A seventh aspect of the present invention provides use of the above copolymer as a flocculant in wastewater treatment.

[0012] Preferably, the wastewater is natural gas purification industrial wastewater.

[0013] The eighth aspect of the present invention provides a method for treating natural gas purification industrial wastewater, wherein a flocculant is added to the natural gas purification industrial wastewater and stirred, wherein the natural gas purification industrial wastewater is organic amine wastewater containing 1-4% sulfate; Preferably, the flocculant is the above-mentioned copolymer.

[0014] Through the above technical scheme, the copolymer of the present invention introduces fluorinated cationic hydrophobic parts into polyacrylamide. Since the fluorinated hydrophobic groups can aggregate, when the copolymer molecules of the present invention are in an aqueous solution, the hydrophobic groups associate intramolecularly and intermolecularly under the action of electrostatics, hydrogen bonds or van der Waals forces, depending on the concentration. When the critical association concentration is reached, the copolymer molecules associate into an aggregate structure, forming a huge three-dimensional network structure, and the apparent viscosity of the solution is greatly increased. By introducing fluorinated hydrophobic groups, the flocculation time of the flocculant can be shortened and the flocculation effect can be improved. The copolymer of the present invention is used as a flocculant, and is added to a 4% sodium sulfate solution together with a conventional cationic polyacrylamide flocculant. The structural changes of the two flocculants in the salt solution are compared. The results are as follows: Figure 1 , 2 As shown, from Figure 1 It can be seen that the copolymer of the present invention still has a three-dimensional network structure in a 4% sodium sulfate solution, and exhibits a strong hydrophobic association effect and good bridging ability. Figure 2 It can be seen that the conventional cationic polyacrylamide flocculant has molecular chain curling under high salt conditions, forming a sheet-like solution structure, and its bridging ability is seriously weakened. The copolymer flocculant of the present invention and the conventional cationic polyacrylamide flocculant were used in the treatment of diatomite suspension simulated high-salt wastewater (containing 4% sodium sulfate), and the transmittance of the supernatant of the simulated high-salt wastewater after treatment was measured by a spectrophotometer. The flocculation treatment effects of the two flocculants on the simulated high-salt wastewater were compared within a certain addition concentration range. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the light transmittance of the supernatant of the simulated high-salinity wastewater treated with the copolymer flocculant of the present invention can reach more than 93%, and when the copolymer flocculant addition concentration is 12 mg / L, the light transmittance of the supernatant reaches a maximum of 99.75%. This is because the copolymer flocculant not only has a positive charge that can neutralize the charge of the diatomaceous earth suspension and cause polymerization, but also has a strong hydrophobic association effect and outstanding bridging ability under sulfate, which promotes the formation of large flocs, thereby better flocculating and settling the diatomaceous earth suspension in the simulated high-salinity wastewater; while the conventional cationic The night light transmittance of the supernatant of the simulated high-salt wastewater after treatment with polyacrylamide flocculant is relatively poor, and with the increase in the dosage of conventional cationic polyacrylamide flocculant, the increase in the light transmittance of the supernatant is not significant, indicating that conventional cationic polyacrylamide flocculants are not effective in flocculating and removing diatomaceous earth suspended matter in simulated high-salt wastewater. This is because the molecular chains of conventional cationic polyacrylamide flocculants curl under high salt conditions, and the positive charges are embedded in the curled molecular chains. At the same time, the bridging ability is severely weakened, and the diatomaceous earth suspended matter in the simulated high-salt wastewater cannot be flocculated and settled well.

[0015] In addition, the perfluoroalkyl-substituted allyl quaternary ammonium salt synthesized as a fluorine-containing cationic hydrophobic monomer has surface activity and can be well dispersed in water, and does not need to add other small molecule surfactants to solubilize the hydrophobic monomer, thus avoiding the use of small molecule surfactants, and the obtained copolymer is easy to post-process and will not cause pollution to the environment; the preparation of the copolymer of the present invention adopts a method of binary copolymerization of aqueous solution, and the preparation process is simple, easy to operate, and convenient to control, and the feeding ratio of the quaternary ammonium salt can be directly adjusted to change the cationic degree of the copolymer, and it is unnecessary to introduce other cationic monomers. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a cryo-scanning electron micrograph of the copolymer prepared in Example 1-1 of the present invention in a 4% sodium sulfate solution; Figure 2 This is a cryo-SEM image of a commercially available cationic polyacrylamide flocculant in a 4% sodium sulfate solution; Figure 3 It is the light transmittance of the supernatant after flocculation and sedimentation of diatomaceous earth suspension simulating high-salt wastewater (containing 4% sodium sulfate) at different dosages of the copolymer prepared in Example 1-1 of the present invention and the commercially available conventional cationic polyacrylamide flocculant. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0019] The first aspect of the present invention provides a perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the quaternary ammonium salt has a structure shown in formula (1): Formula (1), wherein R1 and R2 are independently selected from methyl or ethyl; and n is an integer of 4-11.

[0020] According to the present invention, the quaternary ammonium salt has surface activity, can be well dispersed in water, does not need to add other small molecule surfactants to solubilize the quaternary ammonium salt, and avoids the use of small molecule surfactants. The quaternary ammonium salt of the present invention is used as a fluorine-containing cation hydrophobic monomer and acrylamide to carry out polymerization reaction to obtain a copolymer as a flocculant in industrial wastewater treatment. On the one hand, since the quaternary ammonium salt of the present invention has surface activity, it is not necessary to add other small molecule surfactants to solubilize in the polymerization reaction process, so that the obtained copolymer is easy to post-process and will not cause pollution to the environment; on the other hand, the quaternary ammonium salt of the present invention contains fluorine-containing cations. When carrying out polymerization reaction with acrylamide, the cationic degree of the copolymer can be changed directly by adjusting the feeding ratio of the quaternary ammonium salt, and it is not necessary to introduce other cationic monomers.

[0021] According to the present invention, in order to enable the quaternary ammonium salt as a fluorine-containing cationic hydrophobic monomer to smoothly undergo polymerization with acrylamide only in the presence of an initiator, and to enable the obtained copolymer to have good salt resistance and good flocculation effect when treating industrial wastewater, preferably, the critical micelle concentration of the quaternary ammonium salt is 0.3-7mmol / L.

[0022] According to the present invention, preferably, in formula (1), n ​​is 6, 7 or 9.

[0023] In the present invention, the method for preparing the quaternary ammonium salt can adopt the preparation method provided by the second aspect of the present invention.

[0024] In the present invention, the composition and structure of the hydrophobically associating cationic flocculant can be determined by characterization means such as infrared spectroscopy, or by the feed amount of each material during the preparation process.

[0025] The second aspect of the present invention provides a method for preparing a perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the method comprises: subjecting N,N-dimethylallylamine or N,N-diethylallylamine to a nucleophilic substitution reaction with a perfluoroalkyl halide to obtain the perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the molar ratio of allylamine or its derivative to the perfluoroalkyl halide is 1:1.2-1.5.

[0026] In some embodiments of the present invention, the molar ratio of N,N-dimethylallylamine to perfluoroalkyl iodide is 1:1.3.

[0027] According to the present invention, the solvent for the nucleophilic substitution reaction is acetone and / or 1,4-dioxane.

[0028] In some embodiments of the present invention, the solvent for the nucleophilic substitution reaction is acetone.

[0029] According to the present invention, in order to allow the nucleophilic substitution reaction to proceed completely and obtain the corresponding quaternary ammonium salt, preferably, the temperature of the nucleophilic substitution reaction is 35-55° C. and the time is 6-24 h.

[0030] More preferably, the temperature of the nucleophilic substitution reaction is 40-50° C. and the time is 8-12 h.

[0031] In some embodiments of the present invention, the temperature of the nucleophilic substitution reaction is 40° C. and the time is 12 h.

[0032] According to the present invention, in order to make the prepared copolymer react with most of the negatively charged colloidal particles in the wastewater to perform electrical neutralization, adsorption and bridging, and to be well adapted to the treatment of high-salt industrial wastewater or the removal of impurities in the field of natural gas purification, and to avoid molecular chain coiling and weakening of bridging ability of the flocculant copolymer molecules under high salt conditions, preferably, the perfluoroalkyl halide is selected from one or more of perfluoroheptyl iodide, perfluorooctyl iodide and perfluorodecyl iodide.

[0033] In some embodiments of the present invention, the perfluoroalkyl iodide is perfluoroheptyl iodide, perfluorooctyl iodide or perfluorodecyl iodide.

[0034] According to the present invention, after the nucleophilic substitution reaction is completed, there is also the following post-treatment: the solid powder product obtained by the nucleophilic substitution reaction is repeatedly washed with a solvent, and dried at a constant temperature to a constant weight.

[0035] In some embodiments of the present invention, after the nucleophilic substitution reaction is completed, the washing solvent is diethyl ether and the drying temperature is 35°C.

[0036] The third aspect of the present invention provides a perfluoroalkyl-substituted allyl quaternary ammonium salt obtained by the preparation method of the present invention.

[0037] The fourth aspect of the present invention provides a copolymer, wherein the copolymer comprises: a structural unit A derived from acrylamide and a structural unit B derived from a perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the perfluoroalkyl-substituted allyl quaternary ammonium salt is the perfluoroalkyl-substituted allyl quaternary ammonium salt described in the present invention, and the molar ratio of the structural unit A:structural unit B is 196-199:1-4.

[0038] Preferably, the molar ratio of the structural unit A:structural unit B is 197-199:1-3.

[0039] According to the present invention, in order to make the copolymer react with most of the negatively charged colloidal particles in the wastewater to neutralize the charge, adsorb and bridge, and be well adapted to the treatment of high-salt industrial wastewater or the removal of impurities in the field of natural gas purification, and avoid the molecular chain rolling of the flocculant copolymer molecules under high salt conditions and weaken the bridging ability, preferably, the structural unit A in the copolymer molecule has the structure shown in formula (2), and the structural unit B has the structure shown in formula (3). Formula (2) Formula (3), wherein R1 and R2 are independently selected from methyl or ethyl; n is an integer of 4-11; preferably, n is 6, 7 or 9.

[0040] In some embodiments of the present invention, the molar ratio of structural unit A:structural unit B is 197:3, 989:11, 1989:11, 199:1, 247:3, 1983:17, 4971:29, 989:11, 1987:11 or 497:3, and any value within the range formed by any two of the above values.

[0041] In some embodiments of the present invention, R1 and R2 are independently selected from methyl, and n is 6, 7 or 9, respectively.

[0042] According to the present invention, in order to make the associative effect play a significant role in the bridging ability of the polymer flocculant, preferably, the weight average molecular weight of the copolymer is 2×10 6 -6.5×10 6 g / mol, and the critical association concentration is 0.1-0.3%.

[0043] In some embodiments of the present invention, the weight average molecular weight of the copolymer is 6.5×10 6 g / mol, 4×10 6 g / mol, 3.5×10 6 g / mol, 3×10 6 g / mol, 5×10 6 g / mol, 2×10 6 g / mol, 5.5×10 6 g / mol or 1×10 6 g / mol, and any value within the range formed by any two of the above values; the critical association concentration is 0.1%, 0.21%, 0.25%, 0.28%, 0.13%, 0.18% or 0.3%, and any value within the range formed by any two of the above values.

[0044] The copolymer of the present invention introduces a fluorinated cationic hydrophobic part into polyacrylamide. Since the fluorinated hydrophobic groups can aggregate, when the polymer molecules of the present invention are in an aqueous solution, the hydrophobic groups associate intramolecularly or intermolecularly under the action of electrostatics, hydrogen bonds or van der Waals forces, depending on the concentration. When the critical association concentration is reached, the copolymer molecules associate into an aggregate structure, forming a huge three-dimensional network structure, and the apparent viscosity of the solution is greatly increased. By introducing fluorinated hydrophobic groups, the flocculation time of the flocculant can be shortened and the flocculation effect can be improved. The polymer of the present invention was added as a flocculant into a 4% sodium sulfate solution, and the structural changes of the flocculant in the salt solution were observed. The results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the copolymer flocculant still has a three-dimensional network structure in 4% sodium sulfate solution, showing a strong hydrophobic association effect and good bridging ability.

[0045] In the present invention, the method for preparing the copolymer can adopt the preparation method provided in the fifth aspect of the present invention.

[0046] In the present invention, the composition and structure of the copolymer can be determined by characterization means such as infrared spectroscopy, or by the feed amount of each material during the preparation process.

[0047] A fifth aspect of the present invention provides a method for preparing a copolymer, wherein the method comprises: polymerizing acrylamide and a fluorine-containing cationic hydrophobic monomer in the presence of an initiator and a protective gas to obtain the copolymer.

[0048] According to the present invention, the solution for the polymerization reaction is an aqueous solution, and the solvent used is deionized water.

[0049] Preferably, acrylamide and fluorine-containing cationic hydrophobic monomers are used as solutes, and the mass fraction of the solutes in the polymerization reaction solution is controlled at 20-25%.

[0050] In some embodiments of the present invention, acrylamide and fluorine-containing cationic hydrophobic monomers are used as solutes, and the mass fractions of the solutes in the polymerization reaction solution are 25%, 23%, 22% or 20%, respectively, and any value within the range formed by any two of the above values.

[0051] According to the preparation method of the present invention, in order to make the polymerization reaction proceed smoothly to obtain the copolymer, preferably, the initiator is selected from one or more of sodium persulfate, sodium sulfite, and azobisisobutylamidine hydrochloride; wherein the mass percentage of the initiator is 0.05-0.4% by weight based on the total weight of acrylamide and the fluorine-containing cationic hydrophobic monomer.

[0052] Preferably, the mass percentage of the initiator is 0.1-0.3 wt %.

[0053] In some embodiments of the present invention, the initiator is a composite initiator in which the mass ratio of sodium persulfate, sodium sulfite and azobisisobutylamidine hydrochloride is 2:1:7.

[0054] In some embodiments of the present invention, the mass percentage of the initiator is 0.3%, 0.2% or 0.1%, and any value within the range formed by any two of the above values.

[0055] According to the preparation method of the present invention, in order to enable the prepared copolymer to be used as a flocculant, to undergo electrical neutralization, adsorption and bridging effects with most of the negatively charged colloidal particles in the wastewater, and to be well adapted to the treatment of high-salt industrial wastewater or the removal of impurities in the field of natural gas purification, and to avoid molecular chain coiling of flocculant polymer molecules under high salt conditions and weakening of bridging ability, preferably, the fluorine-containing cationic hydrophobic monomer is the above-mentioned perfluoroalkyl-substituted allyl quaternary ammonium salt.

[0056] According to the preparation method of the present invention, in order to make the copolymer have better water solubility, preferably, the molar ratio of acrylamide to the fluorine-containing cationic hydrophobic monomer is 100:0.5-2.5; Further preferably, the molar ratio of acrylamide to the fluorine-containing cationic hydrophobic monomer is 100:0.7-2.

[0057] In some embodiments of the present invention, the molar ratio of acrylamide to the fluorine-containing cationic hydrophobic monomer is 100:2, 100:1.5, 100:1 or 100:0.7, and any value within the range formed by any two of the above values.

[0058] According to the preparation method of the present invention, in order to make the polymerization reaction proceed smoothly to obtain the copolymer, preferably, the polymerization reaction temperature is 45-55°C and the time is 4-8h; Preferably, the polymerization reaction temperature is 45-50°C and the time is 5-7h.

[0059] In some embodiments of the present invention, the polymerization reaction temperature is 50° C. or 45° C., and the polymerization reaction time is 5 or 7 hours.

[0060] According to the preparation method of the present invention, in order to make the polymerization initiation system at a suitable pH to facilitate the polymerization reaction, preferably, sodium hydroxide is used to adjust the pH of the polymerization reaction solution to 6-9. Preferably, sodium hydroxide is used to adjust the pH of the polymerization reaction solution to 7-8.

[0061] In some embodiments of the present invention, the pH of the polymerization reaction solution is 7 or 8, respectively.

[0062] According to the preparation method of the present invention, after the polymerization reaction is completed, there is also the following post-treatment: washing the reaction product with a solvent for multiple times, placing the washed product in a vacuum oven to dry to constant weight, and grinding it into powder.

[0063] Preferably, the washing solvent is ethanol, and the vacuum drying temperature is 55°C.

[0064] In some embodiments of the present invention, the fluorine-containing cationic hydrophobic monomer is perfluoroheptyldimethylallylammonium iodide, perfluorooctyldimethylallylammonium iodide or perfluorodecyldimethylallylammonium iodide.

[0065] The above copolymer can be obtained by the preparation method provided by the fifth aspect of the present invention. According to the above statement, when the polymer of the present invention is used as a flocculant in the treatment of industrial wastewater, since the copolymer molecules themselves carry a positive charge, the negatively charged colloidal particles in the industrial wastewater can be neutralized and polymerized; and the fluorine-containing hydrophobic groups inside the copolymer molecules are easy to aggregate in aqueous solution, with a strong hydrophobic association effect, and the bridging ability is outstanding under sulfate, which promotes the formation of large flocs, thereby better flocculating and settling suspended matter in high-salt wastewater. In addition, the fluorine-containing cationic hydrophobic monomer synthesized by the present invention has surface activity and can be well dispersed in water. It is not necessary to add other small molecule surfactants to solubilize the hydrophobic monomers, avoiding the use of small molecule surfactants, and the obtained copolymer is easy to post-process and will not cause pollution to the environment; the preparation of the copolymer of the present invention adopts the method of binary copolymerization of aqueous solution, the preparation process is simple, easy to operate, easy to control, and the cationic degree of the copolymer can be changed directly by adjusting the proportion of the fluorine-containing cationic hydrophobic monomer in the monomer composition, without the need to introduce other cationic monomers.

[0066] The sixth aspect of the present invention provides a copolymer prepared by the preparation method provided by the fifth aspect of the present invention.

[0067] A seventh aspect of the present invention provides use of the above polymer as a flocculant in wastewater treatment.

[0068] Preferably, the wastewater is natural gas purification industrial wastewater.

[0069] The eighth aspect of the present invention provides a method for treating natural gas purification industrial wastewater, wherein a flocculant is added to the natural gas purification industrial wastewater and stirred, wherein the natural gas purification industrial wastewater is organic amine wastewater containing 1-4% sulfate; Preferably, the flocculant is the above-mentioned copolymer.

[0070] The copolymer of the present invention is used as a flocculant to carry out flocculation treatment of diatomite suspension simulating high-salt wastewater (containing 4% sodium sulfate), and the light transmittance of the supernatant of the simulated high-salt wastewater after treatment is measured by a spectrophotometer. The flocculation results are as follows: Figure 3 As shown, from Figure 3 It can be seen that under the same experimental conditions, compared with the conventional cationic polyacrylamide flocculant, the night light transmittance of the supernatant of the simulated high-salinity wastewater treated with the copolymer of the present invention can reach more than 93%, and when the copolymer addition concentration is 12 mg / L, the night light transmittance of the supernatant reaches a maximum of 99.75%; while the night light transmittance of the supernatant of the simulated high-salinity wastewater treated with the conventional cationic polyacrylamide flocculant is relatively poor, and with the increase in the dosage of the conventional cationic polyacrylamide flocculant, the increase in the supernatant transmittance is not significant.

[0071] The following examples are used to illustrate the technical solutions of the present invention, wherein the raw materials and reagents used are commercially available, and the room temperature refers to 15-35°C.

[0072] N,N-dimethylallylamine, purity 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; N,N-diethylallylamine, purity greater than 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Perfluoroheptyl iodide, purity greater than 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Perfluorooctyl iodide, purity 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Perfluorodecyl iodide, purity 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Sodium persulfate, analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Sodium sulfite, analytical grade, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Azobisisobutylamidine hydrochloride, purity 97%, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Conventional cationic polyacrylamide flocculant, industrial grade purity, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0073] The structure and composition of the perfluoroalkyl-substituted allyl quaternary ammonium salts were determined by infrared spectroscopy.

[0074] The structure and composition of the copolymer molecules are determined by the feed amounts of each material during the preparation process.

[0075] The weight average molecular weight of the copolymer molecules was determined by gel permeation chromatography.

[0076] The apparent viscosity (or other physicochemical performance parameters) of the copolymer molecules was measured by a Brookfield DV-II rotational viscometer.

[0077] Example 1 (1) Preparation of fluorine-containing cationic hydrophobic monomer perfluoroheptyl dimethyl allyl ammonium iodide: 1 mol of N,N-dimethylallylamine was dissolved in 3 mol of acetone and transferred to a three-necked flask; heated to 40°C under stirring, and then 1.3 mol of perfluoroheptyl iodide was added dropwise into the three-necked flask; after the addition was completed, the mixture was reacted for 12 hours under stirring, and a solid powder product was obtained by suction filtration; the product was repeatedly washed three times with ether and suction filtered to obtain a washed solid powder product; finally, the washed solid powder product was dried in a constant temperature drying oven at 35°C to constant weight to obtain the target product I perfluoroheptyl dimethylallylammonium iodide.

[0078] The surface tension of the target product I was measured, and the critical micelle concentration of the target product I was found to be 7 mmol / L.

[0079] (2) Preparation of copolymer I: Deionized water is added to a polymerization reaction kettle, and the perfluoroheptyl dimethyl allyl ammonium iodide and acrylamide prepared in step (1) are added in sequence under stirring, and the mass fraction of the solute and the pH value of the solution are controlled; nitrogen is then introduced for 30 minutes, and the solution is heated; a composite initiator having a mass ratio of sodium persulfate, sodium sulfite and azobisisobutylamidine hydrochloride of 2:1:7 is then added; a polymerization reaction is carried out; the obtained product is washed with ethanol for multiple times, dried in a vacuum oven at 55°C to constant weight, and ground into powder to obtain the copolymer I.

[0080] The weight average molecular weight of the copolymer I was obtained by measuring the copolymer I by gel permeation chromatography. The results are shown in Table 1.

[0081] By adjusting the reaction conditions in Example 1 (2), copolymers I-1, I-2, I-3 and I-4 can be obtained. The reaction conditions and the compositions and physicochemical properties of the corresponding copolymers are shown in Table 1: Table 1

[0082] Example 2 (1) Preparation of fluorine-containing cationic hydrophobic monomer perfluorooctyl dimethyl allyl ammonium iodide: Dissolve 1 mol of N,N-dimethylallylamine in 3 mol of acetone and transfer to a three-necked flask; heat to 40°C while stirring, then drop 1.3 mol of perfluorooctyl iodide into the three-necked flask; after the addition is complete, react for 12 hours while stirring, and filter to obtain a solid powder product; wash repeatedly three times with ether and filter to obtain a washed solid powder product; finally, dry the washed solid powder product in a constant temperature drying oven at 35°C to constant weight to obtain the target product II perfluorooctyl dimethylallyl ammonium iodide.

[0083] The surface tension of the target product II was measured, and the critical micelle concentration of the target product II was 2.5mmol / L. (2) Preparation of copolymer II: Deionized water is added to a polymerization reaction kettle, and perfluorooctyl dimethyl allyl ammonium iodide and acrylamide prepared in step (1) are added in sequence under stirring, and the mass fraction of the solute and the pH value of the solution are controlled; nitrogen is then introduced for 30 minutes, and the solution is heated; a composite initiator of sodium persulfate, sodium sulfite and azobisisobutylamidine hydrochloride in a mass ratio of 2:1:7 is then added; a polymerization reaction is carried out; the obtained product is washed with ethanol for multiple times, placed in a vacuum oven at 55°C and dried to constant weight, and ground into powder to obtain the copolymer II.

[0084] The weight average molecular weight of the copolymer II was obtained by measuring the copolymer II using gel permeation chromatography. The results are shown in Table 2.

[0085] By adjusting the reaction conditions in Example 2 (2), copolymers II-1, II-2, II-3 and II-4 can be obtained. The reaction conditions and the compositions and physicochemical properties of the corresponding copolymers are shown in Table 2: Table 2

[0086] Example 3 (1) Preparation of fluorine-containing cationic hydrophobic monomer perfluorodecyl dimethyl allyl ammonium iodide: 1 mol of N,N-dimethylallylamine was dissolved in 3 mol of acetone and transferred to a three-necked flask; heated to 40°C under stirring, and then 1.3 mol of perfluorodecyl iodide was added dropwise into the three-necked flask; after the addition was completed, the mixture was reacted for 12 hours under stirring, and a solid powder product was obtained by filtration; the mixture was repeatedly washed three times with ether and filtered to obtain a washed solid powder product; finally, the washed solid powder product was dried in a 35°C constant temperature drying oven to constant weight to obtain the target product III perfluorodecyl dimethylallylammonium iodide.

[0087] The surface tension of the target product III was measured, and the critical micelle concentration of the target product III was found to be 0.3 mmol / L.

[0088] (2) Preparation of copolymer III: Deionized water is added to a polymerization reaction kettle, and the perfluorodecyldimethylallylammonium iodide and acrylamide prepared in step (1) are added in sequence under stirring, and the mass fraction of the solute and the pH value of the solution are controlled; nitrogen is then introduced for 30 minutes, and the solution is heated; a composite initiator of sodium persulfate, sodium sulfite and azobisisobutylamidine hydrochloride in a mass ratio of 2:1:7 is then added; a polymerization reaction is carried out; the obtained product is washed with ethanol for multiple times, placed in a vacuum oven at 55°C and dried to constant weight, and ground into powder to obtain the copolymer III.

[0089] The weight average molecular weight of the copolymer III was obtained by measuring the copolymer III using gel permeation chromatography. The results are shown in Table 2.

[0090] By adjusting the reaction conditions in Example 3 (2), copolymers III-1, III-2, III-3 and III-4 can be obtained. The reaction conditions and the compositions and physicochemical properties of the corresponding copolymers are shown in Table 3: Table 3

[0091] Test Example 1 The copolymer I-1 prepared in Example 1-1 of the present invention and a conventional cationic polyacrylamide flocculant were added to a 4% sodium sulfate solution, and the structure of the copolymer molecules in the solution was determined by cryo-scanning electron microscopy. The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the copolymer of the present invention has a three-dimensional network structure in a 4% sodium sulfate solution, showing a strong hydrophobic association effect and having good bridging ability. Figure 2 It can be seen that the conventional cationic polyacrylamide flocculant undergoes molecular chain curling under high salt conditions, forming a sheet-like solution structure, and its bridging ability is severely weakened.

[0092] Test Example 2 At 25°C, the copolymer I-1 prepared in Example 1-1 was used as a flocculant and a conventional cationic polyacrylamide flocculant was added to a diatomite suspension simulating high-salt wastewater (containing 4% sodium sulfate) to obtain a treated solution containing flocculants of different mass concentrations. After being fully stirred and allowed to stand for a period of time, the upper clear liquid was taken and the transmittance of the supernatant was measured by a spectrophotometer to evaluate the flocculation effect of each flocculant. The results are as follows: Figure 3 shown.

[0093] from Figure 3 It can be seen that the light transmittance of the supernatant of the simulated high-salinity wastewater treated with the copolymer of the present invention can reach more than 93%, and when the addition concentration of the copolymer flocculant of the present invention is 12 mg / L, the light transmittance of the supernatant reaches a maximum of 99.75%. This is because the copolymer flocculant of the present invention not only has a positive charge that can neutralize the charge of the diatomaceous earth suspension and cause polymerization, but also has a strong hydrophobic association effect and outstanding bridging ability under sulfate, which promotes the formation of large flocs, thereby better flocculating and settling the diatomaceous earth suspension in the simulated high-salinity wastewater; while the conventional cationic The night light transmittance of the supernatant of the simulated high-salt wastewater treated with conventional cationic polyacrylamide flocculant is relatively poor, and with the increase of the dosage of conventional cationic polyacrylamide flocculant, the increase of the supernatant light transmittance is not large, indicating that the conventional cationic polyacrylamide flocculant has a poor flocculation and removal effect on the diatomaceous earth suspended matter in the simulated high-salt wastewater. This is because the molecular chain of the conventional cationic polyacrylamide flocculant curls under high salt conditions, and the positive charge is embedded in the curled molecular chain. At the same time, the bridging ability is also severely weakened, and the diatomaceous earth suspended matter in the simulated high-salt wastewater cannot be flocculated and settled well.

[0094] It can be seen from the above embodiments and test examples that the copolymer of the present invention still has a three-dimensional network structure under high salt. When applied to the treatment of high-salt industrial wastewater or the removal of impurities in the field of natural gas purification, the copolymer of the present invention not only carries a positive charge that can neutralize the charge of diatomaceous earth suspension and undergo polymerization, but also exhibits a strong hydrophobic association effect and has good bridging ability. In addition, the fluorine-containing cationic hydrophobic monomer synthesized by the present invention has surface activity and can be well dispersed in water. It is not necessary to add other small molecule surfactants to solubilize the hydrophobic monomer, thus avoiding the use of small molecule surfactants. The obtained copolymer is easy to post-process and will not cause pollution to the environment. The preparation of the copolymer of the present invention adopts a binary copolymerization method of aqueous solution, and the preparation process is simple, easy to operate, and easy to control. The cationic degree of the copolymer can be changed directly by adjusting the proportion of the fluorine-containing cationic hydrophobic monomer in the monomer composition, without the need to introduce other cationic monomers.

[0095] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner, but these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A perfluoroalkyl-substituted allyl quaternary ammonium salt, characterized in that: The quaternary ammonium salt has a structure shown in formula (1), Formula (1), wherein R1 and R2 are each independently selected from methyl or ethyl; and n is an integer of 4-11.

2. The quaternary ammonium salt according to claim 1, wherein The critical micelle concentration of the quaternary ammonium salt is 0.3-7 mmol / L; Preferably, n is 6, 7 or 9.

3. A method for preparing a perfluoroalkyl-substituted allyl quaternary ammonium salt, characterized in that: The method comprises: subjecting N,N-dimethylallylamine or N,N-diethylallylamine to a nucleophilic substitution reaction with a perfluoroalkyl halide to obtain the perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the molar ratio of the N,N-dimethylallylamine or N,N-diethylallylamine to the perfluoroalkyl halide is 1:1.2-1.

5.

4. The preparation method according to claim 3, wherein The temperature of the nucleophilic substitution reaction is 35-55°C and the time is 6-24h; Preferably, the temperature of the nucleophilic substitution reaction is 40-50°C and the time is 8-12h; And / or, the perfluoroalkyl halide is selected from one or more of perfluoroheptyl iodide, perfluorooctyl iodide and perfluorodecyl iodide.

5. A perfluoroalkyl-substituted allyl quaternary ammonium salt obtained by the preparation method according to claim 3 or 4.

6. A copolymer, characterized in that The copolymer comprises: a structural unit A derived from acrylamide and a structural unit B derived from a perfluoroalkyl-substituted allyl quaternary ammonium salt, wherein the perfluoroalkyl-substituted allyl quaternary ammonium salt is the perfluoroalkyl-substituted allyl quaternary ammonium salt according to any one of claims 1-2 and 5, and the molar ratio of the structural unit A:structural unit B is 196-199:1-4.

7. The copolymer according to claim 6, wherein The structural unit A has a structure shown in formula (2), and the structural unit B has a structure shown in formula (3). Formula (2) Formula (3), wherein R1 and R2 are each independently selected from methyl or ethyl; n is an integer of 4-11, preferably 6, 7 or 9; Preferably, the molar ratio of the structural unit A:structural unit B is 197-199:1-3.

8. The copolymer according to claim 6 or 7, wherein The weight average molecular weight of the copolymer is 2×10 6 -6.5×10 6 g / mol, and the critical association concentration is 0.1-0.3%.

9. A method for preparing a copolymer, characterized in that: The method comprises: in the presence of an initiator and a protective gas, polymerizing acrylamide and a fluorine-containing cationic hydrophobic monomer to obtain the copolymer; wherein the fluorine-containing cationic hydrophobic monomer is the perfluoroalkyl-substituted allyl quaternary ammonium salt described in any one of claims 1-2 and 5.

10. The preparation method according to claim 9, wherein: The initiator is selected from one or more of sodium persulfate, sodium sulfite, and azobisisobutyramidine hydrochloride; And / or, based on the total weight of acrylamide and the fluorine-containing cationic hydrophobic monomer, the mass percentage of the initiator is 0.05-0.4 wt %, preferably 0.1-0.3 wt %.

11. The preparation method according to claim 9 or 10, wherein: The molar ratio of acrylamide to the fluorine-containing cationic hydrophobic monomer is 100:0.5-2.5, preferably 100:0.7-2.

12. The preparation method according to claims 9-11, wherein: The polymerization reaction temperature is 40-55°C and the time is 4-8h, preferably the polymerization reaction temperature is 45-50°C and the time is 5-7h; And / or, the pH of the polymerization reaction is 6-9, preferably 7-8.

13. A copolymer obtained by the preparation method according to any one of claims 9 to 12.

14. Use of the copolymer according to any one of claims 6 to 8 and 13 as a flocculant in wastewater treatment.

15. The use according to claim 14, wherein: The waste water is natural gas purification industrial waste water.

16. A method for treating natural gas purification industrial wastewater, characterized in that: Mixing a flocculant with natural gas purification industrial wastewater, wherein the natural gas purification industrial wastewater contains 1-4% sulfate organic amine wastewater; Preferably, the flocculant is a copolymer as described in any one of claims 6-8 and 13.

Citation Information

Patent Citations

  • Preparing method for fluorine containing copolymer flocculating agent

    CN101016182A

  • Hydrophobically associating dimethyl diallyl ammonium chloride cation flocculating agent and preparation method thereof

    CN104163887A

  • Multifunctional fluorinated compound, fluorinated polymers made from the compound, and related methods

    WO2020245724A1